Acute changes in arginine vasopressin, sweat, urine and serum sodium concentrations in exercising humans: does a coordinated homeostatic relationship exist?. Issue 10 (18th September 2008) - Hew-Butler, T; Noakes, T D; Soldin, S J; Verbalis, J G
Abstract : The parallel response of sweat rate and urine production to changes in plasma osmolality and volume support a role for arginine vasopressin (AVP) as the main endocrine regulator of both excretions. A maximal test to exhaustion and a steady-state run on a motorised treadmill were both completed by 10 moderately trained runners, 1 week apart. Sweat, urine and serum sodium concentrations ([Na + ]) were evaluated in association with the plasma concentrations of cytokines, neurohypophyseal and natriuretic peptides, and adrenal steroid hormones. When data from both the high-intensity and steady-state runs were combined, significant linear correlations were noted between: sweat [Na + ] versus postexercise urine [Na + ] (r=0.80; p<0.001), postexercise serum [Na + ] versus both postexercise urine [Na + ] (r=0.56; p<0.05) and sweat [Na + ] (r=0.64; p<0.01) and postexercise urine [Na + ] versus postexercise plasma arginine vasopressin concentration ([AVP]P ) (r=0.48; p<0.05). A significant positive correlation was noted between postexercise [AVP]P and sweat [Na + ] during the steady-state condition only (r=0.66; p<0.05). These correlations suggest that changes in serum [Na + ] during exercise may evoke corresponding changes in sweat and urine [Na + ], which are likely regulated coordinately by changes in [AVP]P to preserve body fluid homeostasis.